2010
DOI: 10.1587/transinf.e93.d.2850
|View full text |Cite
|
Sign up to set email alerts
|

The Time Complexity of Hsu and Huang's Self-Stabilizing Maximal Matching Algorithm

Abstract: SUMMARYThe exact time complexity of Hsu and Huan's selfstabilizing maximal matching algorithm is provided. It is 1 2 n 2 + n − 2 if the number of nodes n is even and 1 2 n 2 + n − 5 2 if n is odd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hsu and Huang [11] proposed a maximal matching algorithm for anonymous networks with arbitrary topology under a central daemon. They showed the time complexity of O(n 3 ) moves, and, it has been revealed that the time complexity of their algorithm is O(n 2 ) moves by Tel [17] and Kimoto et al [13] and O(e) moves by Hedetniemi et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hsu and Huang [11] proposed a maximal matching algorithm for anonymous networks with arbitrary topology under a central daemon. They showed the time complexity of O(n 3 ) moves, and, it has been revealed that the time complexity of their algorithm is O(n 2 ) moves by Tel [17] and Kimoto et al [13] and O(e) moves by Hedetniemi et al [10].…”
Section: Introductionmentioning
confidence: 99%